Estimasi Biaya Perangkat Lunak INLIS LITE 3.0 Perpustakaan Nasional Menggunakan Metode Function Points - Fatimah Chibbatullah; Renny Sari Dewi (JURIKOM (Jurnal Riset Komputer), 2020)
In working on a software project the success of the project must begin with the right planning, if planning is wrong it will cause failure and cost overruns will occur. Therefore it is necessary to estimate the right cost to minimize the risk of over-estimates in software projects. Cost estimation in this study uses the Function Point (FP) method which is a method that measures software by measuring the functional perspective of the software to be built. There are 5 components to calculate the FP matrix, namely External Input (EI), External Output (EO), External Inquiry (EI), Internal Logical File (ILF), External File (EIF). From the research that has been done, the estimated cost of developing INLIS LITE 3.0 software, it is concluded that if Perpustakaan Nasional  want to develop INLIS LITE 3.0  software, it will require approximately IDR798.906.152 or equivalent to effort 18255,91 man / hour.